The personal tutor's handbook - Neville, Lindsey (Palgrave study guides, 2007)
The Personal Tutor's Handbook aims to support academic staff in their role as personal tutors. It offers an insight into staff and student experiences of a university personal tutor system through the use of case studies and considers the impact on both students and staff, reflecting both diversity and equality